PENGARUH JUMLAH UANG BEREDAR TERHADAP INFLASI DAN SUKU BUNGA, SERTA TERHADAP INVESTASI DAN PERTUMBUHAN EKONOMI DI INDONESIA - Karari Budi Prasasti; Edy Juwono Slamet (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2020)
Introduction: Monetary policy is one of the main instruments of macroeconomic policy. The government with monetary policy is able toinfluence the level of economic growth, employment, and the rate of inflation. The one of main monetary policy is controlling the money supply. Money supply has a widespread impact on other macro variables. This study analyzes the effect of the money supply to variable inflationand interest rates, as well as the effects of inflation and interest rates to investment and economic growth in Indonesia. Methods: This study used analysis of TSLS (Two Stages Least Square). The data used in Times Series. Data for the period 1973 until 2012.Results: From the tests showed that there was a significant effect ofmoney supply to inflation and interest rates. Inflation and interest rateshas no effect on investment in Indonesia partially. While there was thesimultaneous effect of inflation and interest rates to Investment inIndonesia. The research showed that significantly the investmentinfluence economic growth in Indonesia.Conclusion and suggestion: Research indicates that the variable in the money supply directly or indirectly have an impact on economic growthin a country, thus appropriate monetary policy should be given such a broad impact in an economy.